HUBUNGAN TINGKAT PENGETAHUAN DENGAN PERILAKU ORANG TUA DALAM UPAYA PENCEGAHAN SIBLING RIVALRY DI DESA KEDUNGJATI KECAMATAN BUKATEJA KABUPATEN PURBALINGGA - Wasis Eko Kurniawan; Suci Khasanah; Muhammad Soali (Viva Medika, 2012)
Sibling rivalry is a jealously competition between sibling. Parent’s knowledge of sibling rivalry prevention is very important to minimalism effects ofsibling rivalry in home. This study conducted to know a relationship betweenparent’s knowledge and behavior to prevent the sibling rivalry in home. Methodused is non-experimental study with cross sectional approach. Sample of this studyconsist of 30 respondent with two sibling < 5 years old with total samplingtechnique. Result of study analyzed with cross sectional approach with SPSS versi11.0. This study showed that respondent still lack of knowledge about siblingrivalry prevention (60%) and respondent behavior to prevent sibling rivalry mostlystill lack too (50%). There is a significant relationship between knowledge andbehavior of parent to prevent sibling rivalry in Kedungjati, Bukateja, Purbalinggadistrict (p= 0,003, r= 0,526).Key Words : knowledge, behavior, sibling rivalry